Arena and (Re)Stabilization of Reog Bulkiyo Dance Cultural Production - Salam, Aprinus; Maulana, Alfian (Universitas Gadjah Mada, 2024)
Contestation among traditional art performances, in the technology and information era, creates complex and diverse challenge to the dance of Reog Bulkiyo. In 1999, the dance had to be stopped following the regeneration and economical problem. Although Reog Bulkiyo has been performed again since 2009, the conditions which makes this dance can be produced is still inexplicable. This article attempts to explain why dance experiencing production and activity stagnation. Pierre Bourdieu’s cultural production theory is used to analyze this problem, while ethnographic qualitative is used as the method. This study found that Reog Bulkiyo dance is in the arena of traditional dance art which has a double-tiered structure. The first structure leads to popular culture, while the second structure leads to art culture. In the first structure, Reog Bulkiyo dance group uses relational capital with relatives, social and Islamic groups to survive in the midst of competition with other popular arts. The dance then gains a relationship with the academy and the state which provides relational, cultural, and symbolic capital in the form of granting intangible cultural heritage status. These two relations give Reog Bulkiyo dance group the opportunity to maintain its cultural production.